Kistadenoma Serosum Ovarii: Laporan Kasus - Wilda Ainia Silmi Kaffah; Dhea Mutiara Karmelita; Nurul Islamy (Medula, 2022)
Ovarian cystadenoma is a benign neoplasm originating from ovarian epithelium, including serous cystadenoma, mucinous cystadenoma, endometrioid, transitional clear cells (Brenner), and stromal epithelial cells. These epithelial tumors account for 60-80% of all ovarian neoplasms. Symptoms experienced by patients with ovarian cystadenoma are quite varied, depending on the type of cyst itself. The management of ovarian cystadenoma is surgical cystectomy with thorough exploration of the intrapelvic and abdominal organs. Further management is usually carried out with histopathological examination to determine the presence or absence of malignancy. Mrs. M, a 57-year-old woman was referred to Abdul Moeloek Hospital with a suspected diagnosis of ovarian neoplasm. The patient was referred for further examination and treatment. Symptoms include a lump in the stomach accompained by lower left abdominal pain since 2 months ago, often feeling nauseous since 5-6 years ago, weight loss is denied. Physical examination revealed a mass in the left lower quadrant. The results of ultrasound examination revealed a cystic mass in the left ovary. The patient was treated with pharmacotherapy and operative left salpingo oophorectomy. Postoperative diagnosis was left ovarian cystadenoma.